Efficiency of application of growth regulator «Chlormequate-chloride» in winter wheat sowing depending on the level of fertilization - Позняк, В. В. (Scientific Progress & Innovations, 2018)
The improvement of technology of growing of winter wheat allows to realize reserve of increase of her productivity. The aim of these researches was establishment of efficiency of complex application of treatment of seed or sowing of winter wheat of sort Spivanka by the growth regulator «Chlormequate-chloride» and different norms of fertilizer of soil by mineral fertilizers (N60Р90К60+N30+N30, N30Р60К30+N30, Р30К20+N30) on a growth, development and forming of harvest of grain at growing on black earth ordinary in the conditions of North Steppe. Treatment of seed or sowing of winter wheat influenced «Chlormequate-chloride» on growth, development and forming of harvest of grain during a spring-summer vegetation at application of all variants of fertilizer of soil. The higher level of harvest is got on a background the most (N60Р90К60+N30+N30) and middle (N30Р60К30+N30) dose of fertilizers. Application of different variants of treatment of «Chlormequate-chloride» provided the increase of harvest of grain of winter wheat within the limits of 3.4–11.6 %. We appeared the most effective variants of application of «Chlormequate-chloride»: treatment of growth regulator in autumn and one or double treatment in spring. Encrustation of seed by «Chlormequate-chloride» influenced positively on forming of harvest of grain of winter wheat also. Difference between variants with one or double treatment by «Chlormequate-chloride» additionally to treatment of sowing in autumn appeared insignificant (within the limits of error of experience). Application of an increase dose of fertilizers (N60Р90К60+N30+N30) in combination with the different variants of treatment of growth regulator did not provide the considerable increase of harvest of grain of winter wheat (on the average of all variants of experience for all years researches it hesitated within the limits of 2.5–4.7 %). At growing of wheat the fertilizer of soil appeared more effective by the dose of fertilizers of N30Р60К30+N30.